The main trends in the study of orthodoxy in the academic periodicals of the Ukrainian SSR of the second half of the 1980s - Savchuk, Ruslan (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. I, Bogoslovie, filosofii͡a, 2023)
The present research focuses on the analysis of the main trends and approaches to understanding the role of Orthodoxy in the historical past, state and public life, which developed and were formed by the scientific and public intelligentsia of the Ukrainian SSR in the second half of the 1980s. It was during this period that those approaches to understanding the role of the Church and religion in the life of the country were formed, which later found its embodiment in the state policy and public rhetoric of independent Ukraine. Modern historiography emphasizes the need for a comprehensive analysis of the Soviet religious narrative, identifying internal factors of Soviet society that determine the direction and nature of secular trends of the late Soviet period. However, the number of specific case studies of the Ukrainian late Soviet narrative is very limited. The present work is intended to fill a historiographical gap in this context. Based on the analysis, it was found out that the understanding of the role of Orthodoxy in public life among the late Soviet scientific and public intelligentsia of the Ukrainian SSR was characterized by an interweaving of complex and contradictory trends. On the one hand, it was characteristic of a rather strong desire to preserve atheistic ideological narratives when considering church-historical and religious studies issues. On the other hand, there is a clear tendency to a critical understanding of atheistic ideology, which, however, very rarely went beyond the protection and protection of "true" Marxism-Leninism. Based on the materials of scientific and popular science periodicals, the process of ideological registration of atheists-religious scholars as the advanced intelligentsia is traced. The increased interest in national issues in church history and culture was combined with the use of old methodological tools in relation to religion. Church periodicals were characterized by the significant influence of the historical features of the perestroika era on the worldview of the clergy and church authors.